A tessitura do gênero textual plano de parto: instrumento de protagonismo em meio à violência obstétrica - Queiroz, Monique Galdino (2023)
Contrary to the technocratic interventionist model of childbirth assistance and the centrality of the medical professional, the motion for the humanization of childbirth seeks to fight against obstetric violence, implementing a series of good practices for a humanized assistance to pregnant women (OMS, 1996; BRASIL, 2002; BRAZIL, 2012). In this sense, humanizing means putting women back as protagonists at the time of childbirth, avoiding unnecessary interventions, while also promoting respect for their physiology, their emotions and their decisions regarding this occasion (TORNQUIST, 2004). Officially appointed by the Ministry of Health in 2017 as a woman's right, the birth plan is an instrument that presents itself as a possibility of providing autonomy to the parturient, becoming a type of letter of intent prepared by the pregnant woman, in which she describes her wishes regarding childbirth. In this context, conceiving the language as a form of social action (BRONCKART, 2012), this research, situated within the field of Applied Linguistics (AL), aims to analyze the sociofunctional and linguistic-discursive characteristics of the childbirth plan genre, investigating to what extent these texts configure the profile of their interlocutors. Thus, we have as a basis, a corpus composed of 12 examples of the genre; a survey and 11 semi-structured interviews with women who wrote and used the text in different assistance contexts. In this investigation, with a qualitative-interpretative nature, we applied the theoretical-methodological assumptions of the Socio-Discursive Interactionism (ISD) also making use of the works of Bazerman (2011) and Bhatia (2001). We also incorporated the concepts from the Discourse Analysis (FOUCAULT, 2008, 2014) and Foucault's discussions (1999, 2021) regarding the birth of Biopolitics and Biopower. We observed, in regarding the analysis of the language action situation, the production context and infrastructure, that the birth plans vary in terms of structure and can be classified into two main types, standardized forms (SF), written by other agent-producers to to be used by pregnant women, and individual plans (IP), written by the women themselves. Furthermore, we found out that the linguistic-discursive characteristics of the genre are linked to its place of circulation and to the representations of its producers about the role of women and doctors in childbirth assistance, which could be seen from the planning of the thematic content and the enunciative mechanisms orchestrated in the birth plans. Moreover, we identified that, when these representations are dissonant, this genre is not all welcomed by the professional, having limited effectiveness in ensuring compliance with the wishes listed by the woman. Hereupon, we pointed out that individual birth plans are still going through a stabilization process within the medical discursive community, since that in addition to the limited reception in hospital care contexts, its initial writing emerges from the initiative of doulas, obstetric nurses, midwives or the woman herself.